Autonomy support from parents and coaches: Synergistic or compensatory effects on sport-related outcomes of adolescent-athletes?. (July 2016) - Gaudreau, Patrick; Morinville, Amélie; Gareau, Alexandre; Verner-Filion, Jérémie; Green-Demers, Isabelle; Franche, Véronique
Abstract: Objectives: This study examined how autonomy support from parents and autonomy support from coaches are associated with sport-related outcomes of adolescent-athletes. Two alternative hypotheses were proposed: (a) a synergistic socialization interaction in which high levels of autonomy support provided by parents and coaches are both needed to obtain the most positive sport-related outcomes, (b) a compensatory-protective interaction in which coaching autonomy support is more important for sport-related outcomes in athletes perceiving lower levels of parental autonomy support. Design: Two studies using prospective designs. Method: Study 1 was conducted with adolescent soccer players ( N = 46) and Study 2 was conducted with gymnasts ( N = 85). In both studies, athletes reported the extent to which they perceived their parents and coaches provided autonomy support. Athletes also completed scales assessing their motivation toward sport (Studies 1 and 2), situational motivation prior to and following a competition (Study 2), and need satisfaction (Study 1). Sport achievement and performance were also assessed in the form of goal attainment (Study 1), self-reported achievement following the competition (Study 2), and flow states (Study 2). Hierarchical moderated regressions were conducted in order to test our competing hypotheses. Results: Analyses provided support for the compensatory-protective interaction hypothesis. Coaching autonomy support was more strongly related to sport motivation, need satisfaction, sport achievement, and flow in athletes who perceived lower level of parental autonomy support. Conclusions: This research program provided support for the study of the interactive effect of perceived autonomy support from distinct socialization agents (i.e., parents and coaches) and its impact on adolescent-athletes. Highlights: Autonomy support from coaches and parents interacted to predict sport-related outcomes. Parental autonomy support moderated the effects of coaching autonomy support. Coaching autonomy support was more consequential under lower parental autonomy support. Coaches were less influential under higher levels of parental autonomy support. Results supported our compensatory-protective interaction hypothesis.